Public Legal Awareness in Combating Corruption - Taufik Taufik (STKIP Taman Siswa Bima, 2025)
Corruption is one of the most serious legal and social problems hampering development in Indonesia. Eradicating corruption cannot rely solely on law enforcement agencies but requires active public participation driven by legal awareness. This study aims to analyze the role of public legal awareness in eradicating corruption and identify forms of participation, challenges, and strategies for strengthening it. This study uses a library research method with a descriptive qualitative approach by reviewing relevant literature, regulations, official reports, and scientific articles on the topic. The research findings indicate that legal awareness is the foundation of public participation, manifested in the rejection of petty corruption, involvement in budget monitoring, reporting through whistleblowing mechanisms, and the internalization of anti-corruption values ​​in the social environment. The main challenges are a permissive culture towards petty corruption, low legal literacy, weak protection for whistleblowers, and inconsistent law enforcement. To overcome these challenges, strategies are needed such as integrating anti-corruption education into the curriculum, conducting extensive regulatory socialization, increasing government transparency, ensuring whistleblower protection, and strengthening a culture of integrity through religious, community, and traditional leaders